METHODS FOR THE DEVELOPMENT OF KNOWLEDGE, SKILLS, AND ABILITIES OF STUDENTS IN THE ORGANIZATIONAL AND TECHNICAL ASPECTS OF WRITING AN ESSAY - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
There is a constant need for knowledge, skills, competencies, and competencies to convey the content and structure of a text. They can be grouped as follows. It is convenient to divide them into four broad groups: a) external organizational and technical aspects of the essay; b) Aspects of the semantic-logical description of the written work (essay); d) knowledge, skills, competencies, and competencies related to the functional and spiritual types of paragraphs in the text; e) Writing skills, competencies, and competencies.